UPAYA PENINGKATAN PELAYANAN KADER MENOPAUSE DALAM MEWUJUDKAN MENOPAUSE SETIA (SEHAT DAN BAHAGIA) - ERVIN RUFAINDAH, ERVIN RUFAINDAH (Poltekkes Kemenkes Jayapura, 2024)
Most women in Indonesia do not know the impacts that can occur when entering menopause. This ignorance is based on the view that menopause is a natural symptom. However, when entering menopause, women experience symptoms such as hot flushes and night sweats, fatigue, insomnia, dry skin and hair, joint aches and pains, headaches, palpitations (fast and irregular heartbeat). , and gain weight. Health cadres function as mobilizers, motivators and providers of information to the community, including in improving the quality of life of menopausal women. The aim of this activity is to increase knowledge, skills of cadres regarding early detection of menopause symptoms and education about menopause, so that it can be applied to menopausal mothers and can provide appropriate information about the symptoms of menopausal mothers so that the quality of life of menopause increases and can realize SETIA (healthy and happy) menopause. ). The solution offered by the service team is providing education to cadres, menopausal mothers, families and community leaders, providing training to cadres, mentoring cadres, providing books on balanced nutrition for menopause, exercise and how to use aromatherapy, learning to make a balanced nutrition menu, improving exercise skills. and how to use aromatherapy. The results obtained were that the age of the majority of cadres was in the range of 45-59 years (pre-elderly) as much as 75%, the increase in the ability of cadres in providing education to the majority of menopause was good at 83.3%, the availability of program facilities and infrastructure such as: pocket books, booklets, videos and a balanced menu module/guide, exercise to prevent osteoporosis and how to use aromatherapy for insomnia.